Dengue virus infection induces broadly cross-reactive human IgM antibodies that recognize intact virions in humanized BLT-NSG mice. (January 2015) - Jaiswal, Smita; Smith, Kenneth; Ramirez, Alejandro; Woda, Marcia; Pazoles, Pamela; Shultz, Leonard D; Greiner, Dale L; Brehm, Michael A; Mathew, Anuja
The development of small animal models that elicit human immune responses to dengue virus (DENV) is important since prior immunity is a major risk factor for developing severe dengue disease. This study evaluated anti-DENV human antibody (hAb) responses generated from immortalized B cells after DENV-2 infection in NOD- scid IL2rγ null mice that were co-transplanted with human fetal thymus and liver tissues (BLT-NSG mice). DENV-specific human antibodies predominantly of the IgM isotype were isolated during acute infection and in convalescence. We found that while a few hAbs recognized the envelope protein produced as a soluble recombinant, a number of hAbs only recognized epitopes on intact virions. The majority of the hAbs isolated during acute infection and in immune mice were serotype-cross-reactive and poorly neutralizing. Viral titers in immune BLT-NSG mice were significantly decreased after challenge with a clinical strain of dengue. DENV-specific hAbs generated in BLT-NSG mice share some of the characteristics of Abs isolated in humans with natural infection. Humanized BLT-NSG mice provide an attractive preclinical platform to assess the immunogenicity of candidate dengue vaccines.